Implementation of the Concept of Islamic Economic Equilibrium in Tagangser Laok Village: Between Spiritual Aspects and Community Welfare - Maisuri, Desi Endang; Jannah, Faridatul; Kamaroellah, R. Agoes (Kawanua International Journal of Multicultural Studies, 2025)
This research examines the implementation of tawazun (equilibrium) principles in Islamic economics in Tagangser Laok Village, Waru District, Pamekasan Regency, Indonesia, to understand how rural communities balance material prosperity with spiritual values in their daily economic activities. Employing a descriptive qualitative approach, data were collected through in-depth interviews with traders, farmers, religious leaders, and small business owners, along with participant observation and document analysis. Findings reveal that the community has internalized tawazun values as foundational to economic behavior, understanding equilibrium as balancing income-earning with religious obligations. A religious leader articulated: "Seeking sustenance must be halal, and one must not neglect worship; otherwise, life is considered unbalanced." This principle manifests concretely in economic practices: traders prioritize honesty despite reduced profits ("If one is honest, even though profit is small, sustenance is more blessed"), farmers practice mutual assistance during hardship ("If a neighbor is in difficulty, we help each other"), and systematic management of zakat and infaq redistributes wealth within the community. The implementation of tawazun generates dual outcomes: enhanced economic welfare through ethical trading and reciprocal support networks, and strengthened spiritual tranquility through alignment of economic activity with religious values. As one business owner reflected: "Income may not be large, but the heart is at peace; that is what we feel as prosperous." Economic relationships become more harmonious, and conflicts are minimized. This study demonstrates that Islamic economic principles can effectively serve as a foundation for equitable, sustainable rural development, offering insights for multicultural societies seeking value-based economic models that balance the material and spiritual dimensions of human welfare.